2010
DOI: 10.1177/030089161009600511
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection of Colorectal Cancer in Elderly Patients

Abstract: Surgical morbidity rate was not affected by age. Cardiovascular and pulmonary comorbid conditions were mainly responsible for the higher morbidity rate reported in the elderly patients, although advanced age, per se, should not be considered a contraindication to laparoscopic colorectal surgery for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The rate of overall morbidity in the present study was 16.4% (85 of 519 patients) and it is comparable with other series in the literature [1112152123]. Surgical morbidity and medical morbidity were similar in both the young and elderly groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rate of overall morbidity in the present study was 16.4% (85 of 519 patients) and it is comparable with other series in the literature [1112152123]. Surgical morbidity and medical morbidity were similar in both the young and elderly groups.…”
Section: Discussionsupporting
confidence: 88%
“…The definition of the elderly was not clearly established in studies; patients older than 65 years [17], 70 years [2122], 75 years [11132324], octogenarians [5121925], and nonagenarians [5] were defined as the elderly groups in the previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, clinical condition (American Classification of Anesthesiologists classification) is frequently impaired among elderly patients with GI cancer affecting postoperative outcome. 42 Given the physical and mental impairment of elderly cancer patients, oncogeriatric patients will even benefit more from a dedicated multidisciplinary approach. 43 The Preoperative Assessment of Cancer in the Elderly (PACE), which incorporates validated instruments, represents a useful tool in evaluating oncogeriatric fitness prior to surgery in elderly colorectal cancer patients, and its use may well be considered in surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures, when used for elderly patients, must be selected with care, considering the magnitude of the surgery and the predicted risk of hospital mortality (9,10); however, postoperative morbidity and mortality increase with age (11)(12)(13)(14)(15). Several studies have reported that MLS demonstrates oncological results and surgical outcomes comparable to that of open surgery (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%